Barras energéticas a base de Theobroma bicolor (macambo), Plukenetia volubilis (sacha inchi), Prunus domestica (guindones) - Rodríguez Cáceres, Jessenia Milagros (2022)
In this present investigation, it was to obtain the technological parameters for the elaboration of energy bars based on macambo of Theobroma bicolor (MACAMBO), Plukenetia volubilis (SACHA INCHI), Prunus domestica (GUINDONES). The research was randomized experimental with 02 factors where factor 1 is the type of syrup with 2 variables and factor 2 is the formulation of the mixture with 3 variables, the classic technology was used in this type of product, the energy bar that sacha inchi; presents a Moisture 12.25%, Ash 5.76%, proteins 13.93%, fat 22.16%, carbohydrates 183.9%, total calories 338.55 kcal, calcium 115 mg, iron 51.20 mg, phosphorus 12 mg, magnesium 109 mg, potassium 343.05 mg, sodium 0.97 mg , and zinc 0.08 mg; through the sensory test with hedonic scales of color, flavor and a high acceptance was determined; the microbiological test determined that it is suitable for human consumption and the stability shown indicates that it can be consumed up to 3 months after its production, this product due to its caloric content, vitamins and minerals would help combat malnutrition